The status of the harbour seal (Phoca vitulina) in Ireland - Cronin, Michelle A (NAMMCO Scientific Publications, 2010)
The status of Ireland’s harbour seal population and its relationship with that of Britain and Western Europe are poorly understood. Prior to 2003, limited research efforts and poor co-ordination of survey methods fell short at providing an accurate assessment of overall distribution and population size on a regional or national scale. However, in August 2003, the Republic of Ireland’s harbour seal population was assessed by means of a geographically extensive survey conducted during the annual moult, providing an up-to-date minimum population estimate and a reliable baseline for future surveys. Trends on a national scale could not be assessed due to absence of a reliable historic population estimate; however there is some evidence of local decreases and increases in harbour seal numbers in Northern Ireland and southwest Ireland respectively. Research effort to date on aspects of the ecology of the harbour seal in the Republic of Ireland is reviewed and current research and management priorities highlighted.